2005
DOI: 10.1074/jbc.m414600200
|View full text |Cite
|
Sign up to set email alerts
|

μ-Calpain Regulates Receptor Activator of NF-κB Ligand (RANKL)-supported Osteoclastogenesis via NF-κB Activation in RAW 264.7 Cells

Abstract: To clarify the role of calpain in the receptor activator of NF-B ligand (RANKL)-supported osteoclastogenesis, RANKL-induced calpain activation was examined by using murine RAW 264.7 cells and bone marrow-derived monocyte/macrophage progenitors. We found that calpain activity increased in response to RANKL in both cell types based on ␣-spectrinolysis and that -calpain, rather than m-calpain, was activated during RANKLsupported osteoclastogenesis in RAW 264.7 cells. Overexpression of -calpain clearly augmented R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 37 publications
4
28
1
Order By: Relevance
“…Our study shows that -calpain is crucial for NO-induced osteoclast motility and that -calpain is regulated by a Ca 2+ signal that requires PKG1, Src and VASP. Our findings are consistent with results from previous studies showing calpain activity in osteoclasts (Lee et al, 2005;Hayashi et al, 2005;Marzia et al, 2006). Earlier research suggested calpain involvement in osteoclast differentiation and function (Lee et al, 2005;Marzia et al, 2006), but here we describe for the first time -calpain activation and Ca 2+ signaling in NO/cGMP-induced osteoclast motility.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our study shows that -calpain is crucial for NO-induced osteoclast motility and that -calpain is regulated by a Ca 2+ signal that requires PKG1, Src and VASP. Our findings are consistent with results from previous studies showing calpain activity in osteoclasts (Lee et al, 2005;Hayashi et al, 2005;Marzia et al, 2006). Earlier research suggested calpain involvement in osteoclast differentiation and function (Lee et al, 2005;Marzia et al, 2006), but here we describe for the first time -calpain activation and Ca 2+ signaling in NO/cGMP-induced osteoclast motility.…”
Section: Discussionsupporting
confidence: 83%
“…The Ca 2+ -release mechanisms involved in these pathways are, for the most part, uncharacterized. Calpain itself is also required for normal osteoclast maturation, and RANK signaling is modified by -calpain (Lee et al, 2005;Marzia et al, 2006).…”
Section: +mentioning
confidence: 99%
“…Another study used a mouse model of hypercholesterolemic nephropathy to demonstrate that macrophages stimulated through the nicotinic acetylcholine receptor ␣1 induced -calpain activation and inflammatory signaling (31). Perhaps most relevant to our findings with SelK are those by Ueda et al showing that m-calpain regulates ␣-crystallins, which are chaperone proteins related to small heat shock family of proteins (30). Similar to our findings with SelK, m-calpain cleavage of ␣-crystallins removes 11 amino acids from the C terminus of the target protein, which inactivates its function.…”
Section: Discussionmentioning
confidence: 51%
“…For example, addition of receptor activator of NF-B ligand (RANKL) to RAW 264.7 mouse macrophages caused an increase in calpain activity (30). In these studies, -calpain was essential for NF-B activation in macrophages induced by RANKL.…”
Section: Discussionmentioning
confidence: 70%
“…In vitro studies (17,30) have demonstrated that both IB␣ and NF-B p65, a subunit of NF-B, are substrates of calpain. In addition, studies (13,35) in nonseptic models have shown that inhibition of IB␣ degradation by calpain inhibitors prevented the translocation of NF-B from the cytosol to the nucleus and inhibited the expression of many NF-B-dependent genes, including TNF-␣.…”
mentioning
confidence: 99%